Sustaining good management practices in public schools: decolonising principals’ minds for effective schools - Buka, Andrea Mqondiso; Matiwane-Mcengwa, Nomzi Florida; Molepo, Maisha (Faculty of Education, University of the Free State, 2017)
While there are perspectives on how to approach decolonisation and transformation of education in schools, the reality is that all rests with individuals and ways that they change their attitudes and mind-set. In the midst of mismatch in the minds of teachers and principals about these two concepts, another confusing term is “democracy” that comes with human rights. The connotation of democracy causes the mind to revert back and propagate the principles of colonisation where individual laxity overwhelms the duties or responsibilities, even accountability to society. In the battle of emancipating individuals’ mind, special reference can be drawn from the general assumption that imperialism aspects, including apartheid, profoundly affected the mind of the oppressed negatively in that during the post-apartheid era the oppressed still entangle themselves tightly. This article attempts to report on the qualitative findings from a pragmatic paradigm study conducted in one education district in the Eastern Cape of South Africa, where face-to-face interviews were carried out with 10 participants (5 chairpersons of school governing bodies and 5 principals) from 5 public schools with document analysis. Thematically analysed findings portray that some school principals enjoyed being ”big baas” (bosses) and displayed unprofessional conducts such as absenteeism or lack of punctuality where nepotism and corruption prevailed.
Keywords: Afrocentric; Corruption; Eurocentric; Learning and nepotism; School principals; Public schools